The Suitability of Word Games for Teaching English Vocabulary Based on Curriculum 2013 - Kamal Yusuf; Cici Dwi S. (IJECA (International Journal of Education and Curriculum Application), 2018)
Digital game becomes more familiar in this young generation. Most of the people particularly young generation love to play game using their personal mobile phone and it seems like to be their habits. In addition, digital games are free for everyone to play as long as they connect to the Internt connection. To exploit this situation, teacher uses it as teaching and learning media to improve students vocabulary in the matter of stduents problem to improve their vocabulary. There are lot of studies which is experimented by digital games to improve vocabulary for their students but only a little talk about the kind of digital game able to be used for improving it. This study is aimed to analyse the digital game especially word game which is available in the play store that suitable for teaching based on the basic competence for seventh grade in curriculum 2013. This study found that only 58,20% of the sutability between the word game and the basic competence.